1999
DOI: 10.1592/phco.19.8.648.31534
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Three Methods of Treating Urogenital Chlamydial Infections in the Emergency Department

Abstract: We attempted to determine the economic impact of three alternatives for the treatment of chlamydial infections in the emergency department: a written prescription for 7 days of doxycycline therapy (D-RX); a prepacked 7-day supply of doxycycline (D-ED); or a single 1-g dose of azithromycin (AZI). Data inputs for the model were obtained from both patient experience and literature sources. Primary health outcomes of the model were number of infection relapses. Economic outcomes were costs for initial treatment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Seven of these compared azithromycin (1 g single dose) with doxycycline (100 mg twice daily for 7 days). [220][221][222][223][224][225][226] All studies assumed 100% compliance for azithromycin in their base-case analysis, but 75-87% for doxycycline. Four studies recommended single-dose azithromycin as the treatment of choice 221,[223][224][225] on costeffectiveness grounds, assuming that incomplete adherence led to more treatment failures.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of these compared azithromycin (1 g single dose) with doxycycline (100 mg twice daily for 7 days). [220][221][222][223][224][225][226] All studies assumed 100% compliance for azithromycin in their base-case analysis, but 75-87% for doxycycline. Four studies recommended single-dose azithromycin as the treatment of choice 221,[223][224][225] on costeffectiveness grounds, assuming that incomplete adherence led to more treatment failures.…”
Section: Treatmentmentioning
confidence: 99%
“…Petitta and colleagues found that both azithromycin and a prepacked course of doxycycline reduced infection rates compared with a prescription for doxycycline, and acknowledged that cure is likely even without completing the 7-day course. 220 …”
Section: Treatmentmentioning
confidence: 99%
“…Hence, the higher cost of azithromycin must be balanced against the medical cost of potential complications of persistent infection that could result from treatment failure in noncompliant doxycycline-treated patients. Decision analysis studies have demonstrated that single-dose azithromycin is just as costeffective as-or more cost-effective than-a 7-day course of doxycycline [9,10].…”
Section: What Are the Considerations For Recommending Doxycycline Vermentioning
confidence: 99%
“…For all other health states, we used population sex-and age-adjusted weights derived from time tradeoff estimates reported in the literature. 40,76 The direct medical and nonmedical cost estimates and plausible ranges used in the base case analysis 3,5,25,53,57,59,63,64,[77][78][79][80][81][82][83] are shown in Table 2. The cost of a pelvic examination ($25.35), including the cost of materials and time costs of an emergency physician (15 minutes) and a registered nurse (17 minutes), were derived from published estimates and from an expert panel.…”
Section: Analytic Overviewmentioning
confidence: 99%
“…6 -10 Despite dramatic declines in rates throughout the 1980s and much of the 1990s, since 1998, the numbers of reported cases of gonorrhea have changed little, and recent evidence of persistently high gonorrhea rates among adolescents and minorities in some inner-city settings suggests the need for improved infection control efforts. 4,[11][12][13][14][15][16][17][18][19][20][21] Many uninsured or medically underserved women attend inner-city emergency departments (EDs) as a usual source of health care, 5,[22][23][24][25][26][27][28][29][30] rendering EDs potentially high-yield screening opportunities for detecting and treating gonococcal infections and other sexually transmitted diseases (STDs). 23,26,28 -31 However, gonorrhea screening in EDs has been hampered by logistical difficulties in specimen collection (i.e., the complaints bringing patients to the ED did not warrant pelvic examination) and inability to provide follow-up care.…”
mentioning
confidence: 99%